Non-Wood Forest Products of Asia Knowledge, Conservation and Livelihood - Rashid, A. Z. M. Manzoor; Khan, Niaz Ahmed; Hossain, Mahmood (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book highlights the importance of non-wood forest products (NWFPs) and their crucial role in sustaining the livelihood of rural and indigenous communities in Asia. The authors depict how the preservation of forests and the associated major non-wood resources may provide an important avenue to reduce poverty. The local practices and knowledge on harvesting NWFPs are often rooted in tradition, and vary from one region to the other. This made it difficult to develop and establish research focus on a greater scale in the past. Readers of this volume will gain an often-missed, broader perspective from these new studies. The authors put a special emphasis on the nexus between conservation and livelihood from an Asian point of view. This addresses a knowledge gap in the current literature and offers important clues on conducting similar research around the world. The volume provides a useful reference guide for the relevant researchers, practitioners and policy makers.
1. Legal and policy issues sustaining conservation and livelihood through non-wood forest products: A global perspective -- 2. Traditional ecological knowledge in non-wood forest products management and biodiversity conservation: A focus on Chittagong Hill Tracts -- 3. Historical and contemporary reflections on non-wood forest products -- 4. Non-wood forest product of the Sundarbans, Bangladesh: the context of management, conservation and livelihood -- 5. Role of non-wood forest products in Bhutan's quest for Gross National Happiness: An overview. 6. Non-wood forest products and agroforestry of Sri Lanka: Status, challenges and way forward -- 7. Consumption and marketing pattern of non-wood forest products in a rapidly changing world: Insights from north-east Bangladesh -- 8. Initiatives to enhance sustainability and productivity of bamboo in the Philippines -- 9. Non-wood products of Malaysian mangrove: contribution to livelihood and conservation -- 10. Plants in the Tribal life of Arunachal Pradesh with Special Reference to Tangsa Community, India.
Keywords: Forestry; Biodiversity; Economic policy; Social policy; Forestry; Biodiversity; Socio-Economic Policy